Fluid flow in crustal fault zones with varying lengthwise thickness: application to the Margeride fault zone (French Massif Central) - Emmy Penhoët; Laurent Arbaret; Laurent Guillou-Frottier; Hugo Duwiquet; Charles Gumiaux; Mathieu Bellanger (Geothermal Energy)
Abstract Crustal fault zones, holding promise as potential geothermal reservoirs, remain largely untapped and unexplored. Located in the southern Massif Central, France, the Margeride fault zone (MFZ) varies in thickness (lateral extension perpendicular to the fault plane) from 100 m to over 2500 m. Reactivated several times under different stress regimes since the Variscan orogeny, this zone is characterized by an intense alteration and fracturing. As a result, the multiple reactivation of the fault zone has maintained permeability, leading to favourable conditions for fluid circulation. Structural measurements and geological cross sections were used to precisely constrain thickness and geometry of the fault zone. North of the MFZ, the Coren thermal spring indicates reservoir temperatures of about 200–250 °C, hinting at the possible existence of a temperature anomaly. To investigate this geothermal potential, 3D numerical models simulating fluid circulation within a fault zone were conducted. Various configurations were explored, altering fault zone thickness and permeability for two key geometries. The first geometry, which manipulated the width of the fault zone along its length, demonstrated a direct correlation between fault zone thickness and amplitude of thermal anomaly. Thinner faults (< 500 m) exhibited multiple weak positive thermal anomalies, while thicker faults (> 500 m) tended to develop a single, substantial positive thermal anomaly. In the second examined geometry, where fault zone thickness increased longitudinally, a consistent positive temperature anomaly emerged at the thickest section of the fault zone. Depending on the permeability value, an additional anomaly may develop but will migrate laterally towards the thinnest part of the fault zone. This multi-disciplinary approach, combining numerical modelling and field measurements, presents a predictive methodology applicable to geothermal exploration in analogous basement domains. In our case, it has shown that the northern end of the Margeride fault zone could represent an area that needs to be explored further to assert its high geothermal potential. Our numerical models will increase understanding of how fault width and geometry impact the geothermal potential of the Margeride fault zone and similar areas in crystalline basement.